(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To establish the in-house specifications of “Nhat gan linh” capsules have been established. Materials and Methods: Investigate the in-house specifications of Nhat gan linh capsules including criteria: appearance, loss on drying, disintegration test, dosage uniformity, identification, quantitative assay, heavy metals and microbial limits. Results: Appearance: Hard capsules with brown color, bitter sweet; Loss on drying: no more than 6%; Test for disintegration: less than 15 minutes; Uniformity of dosage units: the average drug in capsules about 500mg ± 7.5%. Identification: qualitative assay of berberin and saikosaponin A in Nhat gan linh capsules using HPLC. Quantitative assay: the content of berberin and saikosaponin A each capsule not less than 40 and 2 mg/capsule, respectively. Heavy metals: not more than 10 ppm. Microbial limit: Satisfaction of Vietnamese Pharmacopoeia (Appendix 13.6- level 4). Conclusions: The study has successfully developed the in-house specifications of Nhat gan linh capsules.